On the problem of research schools in the library science - A. N. Vaneev; V. S. Kreydenko; V. A. Borodina; M. N. Kolesnikova; V. V. Orlov (Библиосфера)
Scientists of the Department of Library Science and Reading Theory of St. Petersburg State University of Culture and Arts express their points of view on the problem of studying and definition of the library science research schools (RS). Today there are no generally accepted methods and description of RS as a socio-cultural institution, there is no unified strategy for their development in the library science, there is no consensus on what meaning should be invested in the «research school» notion. It’s multivariate; it is impossible to reduce it to a single unified definition yet. There are different RS in the library science, which are based on various features (mostly combinations of them). Their analysis allows us to state that this set defines a specific RS. One of the signs proposed is territorial, joining scholars engaged in research within a certain area (region, city, academic city, etc.) into a single scientific community. A common proposal, to consider RS only as an informal association of scientists unrelated to and independent on the administrative work of the head, is inconclusively. No less controversial proposal is to consider the disciples only those scientists who were able to defend the theses, because some graduate students were not able to do it by domestic and everyday problems. It’s doubtful the desire to correlate a research school with the number of dissertations defended under the guidance of a supervisor, as the number of graduate students is not always dependent on the scientific head, but of the plan of admission to post-graduate school. As for RS it’s more important not the number of students, but what new things they introduce in the studied problem. Dissertation subjects do not always fit into frames of the same problem. This phenomenon is quite typical for the library science and reflects the leading library researchers focusing on studying several scientific problems simultaneously. Expanding horizons of researcher interests enriches the theoretical foundation of library science, and attempts to «fix» the research school to the only direction, tabooing evolution of a research program of RS will lead to stagnation with the resulting consequences sooner or later. Widening the circle of scientific interests in the course of researcher professional activities is natural and gives additional arguments in favor of understanding the temporal «mobility» of the RS concept, the possibility to regard an investigator to different schools at diverse stages of his exploration, integrating approaches of different schools in papers of a scientist, especially for studying complex multi-dimensional phenomena. Despite the existing investigations on RS in the library-information sphere, there is no clarity on distinguishing one school from the others. There are three basic directions in specialty 05.25.03 «Library Science, Bibliographic Science and Bibliology», according to which Ph.D. thesis are defended at the library-information faculties. Scientific disciplines are branched based on interconnectivity of these sciences within mentioned three basic directions. But the analysis of formation and development of library-information activity sphere in the historical aspect shows «diving» of individual scientists, research groups into scientific problems, which previously were assigned by specific departments, «intrusion» into adjacent areas and their «capture». This is facilitated by the reorganization and renaming of departments, restructuring curricula. Objectivity and integrity in RS studying is important not to «speculate» on such schools and their identification, categorical assertions that one scientist has a school, and the other hasn’t. Much due to the problem delicacy remains unsaid, intentionally bypassed, and even distorted in the process of interpreting the specific merits of a certain RS. Understanding and description of RS on the basis of different approaches is the most productive way to develop this problem of the science of science. By way of posing the problem one can identify research groups with RS signs emerged at the Department of Library Science in N. K. Krupskaya Leningrad State University of Culture in Soviet times and continued their development later: RS on activity with readers by V. F. Sakharov, nowadays it’s a school of library-information servicing in St. Petersburg State University of Culture and Arts under the guidance of professors V. S. Kreydenko and V. A. Borodina, each leads a specific direction within the school; RS on library science by professor A. N. Vaneev. Schools of library scientists by G. G. Firsov and B. Yu. Adelman are to be studied. It’s suggested that it must be preferable to call schools of not on research directions or problems, but using names of their founders and leaders - «L. B. Khavkina’s school», «Yu. V. Grigoriev’s school», «V. F. Sakharov’s school», «Yu. N. Stolyarov’s school» etc.